Similar weight loss and maintenance in African American and White women in the Improving Weight Loss (ImWeL) trial - Kinsey, Amber W. (Ethn Health, 2018)
OBJECTIVE: African Americans (AA) are often underrepresented and tend to lose less weight than White participants during the intensive phase of behavioral obesity treatment. Some evidence suggests that AA women experience better maintenance of lost weight than White women, however, additional research on the efficacy of extended care programs (i.e. continued contacts to support the maintenance of lost weight) is necessary to better understand these differences. METHODS: The influence of race on initial weight loss, the likelihood of achieving ≥5% weight reduction (i.e. extended care eligibility), the maintenance of lost weight and extended care program efficacy was examined in 269 AA and White women (62.1% AA) participating in a 16-month group-based weight management program. Participants achieving ≥5% weight reduction during the intensive phase (16 weekly sessions) were randomized to a clustered campaign extended care program (12 sessions delivered in three, 4-week clusters) or self-directed control. RESULTS: In adjusted models, race was not associated with initial weight loss (p = 0.22) or the likelihood of achieving extended care eligibility (odds ratio 0.64, 95% CI [0.29, 1.38]). AA and White women lost −7.13 ± 0.39 kg and −7.62 ± 0.43 kg, respectively, during initial treatment. There were no significant differences in weight regain between AA and White women (p = 0.64) after adjusting for covariates. Clustered campaign program participants (AA: −6.74 ± 0.99 kg, White: −6.89 ± 1.10 kg) regained less weight than control (AA: −5.15 ± 0.99 kg, White: −4.37 ± 1.04 kg), equating to a 2.12 kg (p = 0.03) between-group difference after covariate adjustments. CONCLUSIONS: Weight changes and extended care eligibility were comparable among all participants. The clustered campaign program was efficacious for AA and White women. The high representation and retention of AA participants may have contributed to these findings.